Relasi Penafsiran Amin Al-Khuli tentang Puasa dalam Al-Quran dengan Kondisi Sosiologis dan Psikologis - Ridlo, Muhammad Abdurrasyid; Amanaturrahman, Amanaturrahman; Kholis, Iskandar (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The literary exegesis of the Qur'an developed by Amin Al-Khuli offers a new approach to interpreting the sacred text as a response to critiques of classical exegesis and modern cultural and intellectual developments. This study aims to explore the evolution of Qur'anic interpretation in the contemporary era, with a focus on Amin Al-Khuli’s literary exegesis of the verses on fasting and its relevance to the sociological and psychological conditions of Muslims who fast. The research uses a qualitative approach with library research methods, where data is gathered through literature review and analyzed using techniques of inventory, classification, and interpretation. The findings reveal that Al-Khuli’s literary exegesis provides a deeper and more contextual understanding of the fasting verses, linking the aspects of language and Qur'anic meaning with contemporary social and psychological conditions. The conclusion of this research is that the literary exegesis approach not only enriches the understanding of the text but also offers practical solutions to the challenges faced by Muslims in fasting practices. Recommendations for future research include conducting field studies to collect more empirical data and exploring the integration of literary exegesis with other interpretive approaches for broader application in Muslims' daily lives.